EDUKASI PENCEGAHAN STUNTING PADA ANAK USIA PRA SEKOLAH DIWILAYAH KERJA PUSKESMAS PALEMBANG - Indra Frana Jaya KK; Sasono Mardiono (PT. Jurnal Center Indonesia Publisher, 2026)
Stunting remains a chronic nutritional problem of major concern in Indonesia. Preschool-aged children are particularly vulnerable to the ongoing impacts of stunting. The nutritional process involves the intake of nutrients that are digested and absorbed by the digestive tract, then used for energy, the formation and repair of body tissues, and the regulation of biochemical and hormonal functions. The MMD was attended by 25 people, consisting of community members, health workers, lecturers, and students. Participants provided input on efforts to prevent infectious diseases, particularly stunting, which has been experienced by several residents. The educational activity took place on Saturday at 11:30 a.m. WIB, involving families with a history of stunting. This activity aimed to improve families' health care skills related to stunting prevention. Programs or interventions implemented to prevent stunting must carefully consider both input and process aspects to achieve optimal output and must involve all parties, from mothers of toddlers to cross-sectoral stakeholders